THE SECRETS BEHIND CHILDREN'S RAPID LANGUAGE ACQUISITION: A PSYCHOLINGUISTIC PERSPECTIVE ON EARLY CHILDHOOD LEARNING - Cinta Yulistra Tindaon; Bernieke Anggita Ristia Damanik (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research explores the process of rapid language acquisition in children aged 0–6 years, focusing on the psycholinguistic perspective. The study aims to uncover the primary factors influencing language learning and the mechanisms that facilitate it. Using a literature review approach, data were gathered and analyzed from academic journals, books, and case studies. The results indicate that language development is driven by biological factors, such as neuroplasticity, and environmental influences, including parental communication patterns like motherese. Furthermore, declarative and procedural memory systems play a crucial role in building vocabulary and mastering grammar. Unlike adults, children learn language more effectively through natural interactions in daily life. This research contributes to the creation of appropriate strategies for early language education. Future studies could investigate multilingual language development and the effects of digital technology on children’s language acquisition.